ASAL MULA KONFLIK MENURUT ALKITAB - Gerry C. J. Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2013)
Conflict is not related with good or bad, rich or poor, educated or not educated. Conflict is simply a fact of life. Always felt and seen in every aspect of life. Where does conflict begin? Does it occur simultaneously with the creation of this world? Does God create the conflict in this world? The Bible clearly shows it all. 1. God never created the conflict. 2. The conflict originated in heaven through pride and jealousy an angel known as Lucifer against God. 3. This conflict also brought him into the world that is the work of God's creation. 4. As long as there is still sin in this world then the conflict will continue to exist.